상악에 발생한 국소 소아기 해면상 치은증식증: 증례보고 - 길도건; 정영곤; Do-Geon Gil; Yeong Kon Jeon (대한구강악안면병리학회지, 2024)
Localized juvenile spongiotic gingival hyperplasia (LJSGH) is an exceedingly rare gingival disease. Most LJSGH occur in children, predominantly on the labial gingiva of the maxilla, and exhibit clinical manifestations similar to pyogenic granuloma or puberty gingivitis. This report presents a case of LJSGH. A 15-year-old male referred for evaluation of red lesions on the labial gingiva of the maxillary anterior teeth. Clinical examination revealed redness and swelling of the labial marginal gingiva, with no associated pain. After an incisional biopsy, the lesion was histopathologically diagnosed as LJSGH. We present this case to suggest that LJSGH should be considered in the differential diagnosis of patients presenting with painless gingival redness and swelling. We also report that we have obtained satisfactory aesthetic results by applying CO2 laser to LJSGH.